Structural consequences of the range of the interatomic potential - A menagerie of clusters - Doye, J; Wales, D (1997)
We have attempted to find the global minima of clusters containing between 20 and 80 atoms bound by the Morse potential, as a function of the range of the interatomic force. The effect of decreasing the range is to destabilize strained structures, and hence the global minimum changes from icosahedral to decahedral to face-centred-cubic as the range is decreased. For N > 45, the global minima associated with a long-ranged potential have polytetrahedral structures involving defects called disclination lines. For the larger clusters, the network of disclination lines is disordered and the global minimum has an amorphous structure resembling a liquid. The size evolution of polytetrahedral packings enables us to study the development of bulk liquid structure in finite systems. As many experiments on the structure of clusters only provide indirect information, these results will be very useful in aiding the interpretation of experiment. They also provide candidate structures for theoretical studies using more specific and computationally expensive descriptions of the interatomic interactions. Furthermore, Morse clusters provide a rigorous testing ground for global optimization methods.